Letter to the editor regarding the article "The global distribution of acute unintentional pesticide poisoning: estimations based on a systematic review" - S. Eliza Dunn; Jennifer E. Reed; Christoph Neumann (BMC, 2021)
Abstract We read with interest the article entitled "The global distribution of acute unintentional pesticide poisoning: estimations based on a systematic review". We wholeheartedly agree that it is important to evaluate the extent of this issue. We would like to understand the numbers provided in this article, which appear to overestimate the global burden of pesticide poisonings. We also feel that addressing the benefits of these chemistries is important for a complete evaluation.